EXPERIMENTAL STUDY OF THE SEQUENT DEPTH RATIO OF THE HYDRAULIC JUMP IN A STRAIGHT COMPOUND RECTANGULAR CHANNEL - Riguet, F.; Debabeche, M; Ghomri, A. (Journal of Fundamental and Applied Sciences, 2019)
The aim of this experimental study is to analyze the sequent depth ratio of the hydraulic jump evolving in a straight compound rectangular channel. A functional relationship, in non-dimensional terms, linking together the different characteristics of the jump, is obtained.